Preparation of hybrid Ag₂O/TiO₂ photocatalyst responsive towards UV light (effect of incubation time): article - Ahmad Halil, Anis Haziqah; Lim, Ying Chin (2017)
The objectives of the present study are to prepare hybrid Ag₂O/TiO₂ photocatalyst by wet impregnation method at different incubation time as well as to determine its photocatalytic performance on the degradation of Methyl Orange (MO). Ag₂O/TiO₂ photocatalyst was prepared by mixing 5 wt% of Ag with TiO₂ in 50 mL of distilled water. The solution was incubated for one, two, four, eight and 24 hours at 70 °C and was washed and calcined overnight in a furnace at 450 °C. The degradation of MO was conducted by adding 1 g of photocatalyst in 200 mL of MO solution with concentration of 10 ppm. The solution was supplied with oxygen and was stirred during the reaction for three hours with the presence of UV light. The presence of Ag on TiO₂ surface was confirmed from the characterization analysis. The degradation of MO increased until eight hours of incubation time and then decreased. Thus, the Ag₂O/TiO₂ photocatalyst with eight hours of incubation time was the optimum photocatalyst in which the percentage removal of MO reached 84.94%. It also obtained the highest rate coefficient as well as coefficient of determination, which were 0.01078 min-1 and 0.992, respectively. The half-life calculated was 64.29 minutes.